Evaluation of the groundwater quality in the Alcochete area using GIS - Cavaleiro, Victor (2012)
Most of the water needed for domestic, agricultural, recreational and industrial activities in the municipality of Alcochete (Portugal) comes from groundwater sources. However, doubts remain on the state of their quality and suitability for current uses. The study of the hydrogeochemistry allows establishing relations between the aqueous and geological environment, reflecting the influence of local geology and soil water quality. Given the amount and complex information that was necessary to collect, calculate, analyze and interpret the use of Geographic Information Systems (GIS) was of great use to georeference data, create relational data bases and generate maps of suitability for use of groundwater [1].